(untitled) - Katz, Donald (Holbrook, Mass, 1994)
Nike understood the power of imagery and knew how to market those images all over the world. A truly global corporation, Nike relied on capital from Japan to manufacture shoes in Asia sold to one out of every four athletic-shoe buyers in Europe. Katz follows Nike all over the world, taking us from a 19-year-old Korean gluing shoes in a factory, to an advertising wunderkind in Oregon creating the legendary "Bo Knows" campaign, to the fanatical Nike kids who rush into stores the day new shoes hit the street. Along the way, Katz describes the creation and design of Nike shoes, revealing technology worthy of a James Bond movie. He examines the charges leveled against Nike: that the company is exploiting Asian peasants, corrupting younger athletes, and recklessly stirring consumer fever in urban America. He also discusses the corporate spirit and strategies that have made Nike one of the great business stories of the late 20th century.
Keywords: Sporting goods industry,Sports; History,Marketing; United States,United States